Moving Toward a Smoke-free Campus: A Survey of Students’ Knowledge, Behavior, and Opinions - Ülken Tunga Babaoğlu; Hüseyin İlter (Thoracic Research and Practice)
OBJECTIVE: This study examines the tobacco and product use status of university students, their awareness of smoke-free campuses, and the relationship between tobacco use awareness and tobacco use status. MATERIAL AND METHODS: Data were collected using a questionnaire for students (n = 15.515) who continued their education at a state university. The questionnaire consisted of three sections: sociodemographic, tobacco and product use behaviors, and a Smoke-free Campus Awareness Scale (SCAS). The chi-square test was used for categorical variables, and the Kruskal-Wallis test was used for continuous variables. RESULTS: 28.5% of the university students were active smokers, and 48.7% were exposed to passive smoking on campus. When the SCAS scores were compared according to the smoking status of the students, never smokers (median: 44.0, Q1=36.0-Q3=48.0), active smokers (median: 27.0, Q1=20.0-Q3=36.0), and recent quitters (median: 33.0-Q1=11.0-Q3=43.0) (P < 0.001). SCAS scores were compared according to gender; the median score of female students (Q1=31.0-Q3=46.0) was statistically higher than that of male students (Q1=19.0-Q3=44.0). Non-smokers were found to be statistically more uncomfortable with being exposed to secondhand smoke on campus than smokers (P < 0.001). CONCLUSION: Most students were unaware of the smoke-free campus policy but were aware that passive smoking is an important public health problem. The fact that male students and smokers oppose implementation requires investigation of the reasons for these attitudes in future studies, and monitoring tobacco use trends after implementation is important to effectively evaluate smoke-free campus implementation.